ESTIMATION MODEL OF POTATO FARMING PRODUCTION FUNCTION IN KERINCI REGENCY, JAMBI PROVINCE INDONESIA - Nainggolan, Saidin; Effran, Endy; Fathoni, Zakky (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This study aims to estimate the model of potato farming production function in Kerinci Regency, Jambi Province. The estimation of the production function model uses the Cobb-Douglas production function model, the transcendental production function model, and the log-log inversion production function model. The best production function model of the analysis that is able to explain the physical relationship between inputs and potato farming output is the Cobb-Douglas production function model with the value of the determination coefficient adj-R2 = 0.8566 [85.66 %] for granola and for cipanas varieties the determination coefficient adj-R2 = 0.8972 [89.72 %] . The Cobb-Douglas production function model was chosen as the best function because it showed a high adj-R2 value and a t-test of each significant predictor variable. The estimation of the production function model of the Cipanas potato farming function is only a Cobb-Douglas production function model that is able to explain the logical, factual and theoretically acceptable technical relationship to explain the influence of production inputs on production. The sum of all input parameters for granola potato farming production was obtained ∑βi = 0.9689.< 1. Indicates that granola potato farming is in area I (Decreasing Return to Scale). In the cultivation of cipanas potato varieties, ∑βi = 0.9669 < 1. It indicates that the cultivation of cipanas potato varieties is in area II (decreasing Return to Scale). The technical efficiency of both potato varieties is relatively low, which means there is still great potential for increased productivity.